Answer:
its a simple for me
Step-by-step explanation:
2+144 i
Answer:
The procedure for this case is add three, then divide by 5.
Step-by-step explanation:
if y=5x-3
to find the inverse, we exchange x and y then solve for the new y.
x=5y-3 add 3
x+3 = 5y divide by 5
(x+3)/5 = y
or
inverse, y=(x+3)/5
The procedure for this case is add three, then divide by 5.
You can find the answer on quizzez i promise you
Answer:
Step-by-step explanation:
![13(6x-5)-x=13-2(x+1)\\78x-65-x=13-2x-2\\77x-65=11-2x\\77x+2x=11+65\\x=76/79\\x=0.9620](https://tex.z-dn.net/?f=13%286x-5%29-x%3D13-2%28x%2B1%29%5C%5C78x-65-x%3D13-2x-2%5C%5C77x-65%3D11-2x%5C%5C77x%2B2x%3D11%2B65%5C%5Cx%3D76%2F79%5C%5Cx%3D0.9620)
Answer:
9√10 (nine square root ten)
Step-by-step explanation:
(3√3 .√5.√3.)√2
= (3√3*3.√5)√2
=(3*3.√5)√2
=(9√5) √2
=9√5*2
=9√10